We, the People - Mishkova Diana (Central European University Press, 2009)
Analyzes the processes of nation-building in nineteenth and early-twentieth-century south-eastern Europe. A product of transnational comparative teamwork, this collection represents a coordinated interpretation based on ten varied academic cultures and traditions. The originality of the approach lies in a combination of three factors: [a] seeing nation-building as a process that is to a large extent driven by intellectuals and writers, rather than just a side effect of infrastructural modern...